THE EFFECT OF PRODUCTIVE ZAKAT, BUSINESS CAPITAL, PRODUCTION COSTS, AND LABOR ON THE INCOME OF AGRIBUSINESS-BASED MSMEs SUPPORTED BY LAZISMU IN BANYUMAS REGENCY - Irmawati; Sukmaya, Syahrul Ganda; Rachmah, Malinda Aptika (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The relatively high poverty rate in Banyumas Regency is partly influenced by the high unemployment rate. The existence of MSMEs is one sector that has the potential to provide a solution to this problem. However, many MSME players still face obstacles, especially in terms of access to capital. This study was conducted with the aim of identifying the characteristics of MSMEs that receive productive zakat and analyzing the influence of productive zakat, business capital, production costs, and labor on the income of agribusiness-based MSMEs under the guidance of LAZISMU Banyumas Regency. The research method used was a quantitative approach with an explanatory survey design. The data collected consisted of primary and secondary data through questionnaires, interviews, and documentation studies. The research population included 167 owners of agribusiness-based MSMEs who had received benefits from the productive zakat program, with a research sample of 63 MSMEs selected using a simple random sampling method. Data analysis was conducted through descriptive analysis, classical assumption tests, and multiple regression using SPSS software version 26. The results of the study indicate that productive zakat, business capital, production costs, and labor simultaneously have a significant effect on increasing MSME income.